The second Randomised Evaluation of the Effectiveness, cost-effectiveness and Acceptability of Computerised Therapy (REEACT-2) trial : does the provision of telephone support enhance the effectiveness of computer-delivered cognitive behaviour therapy? : a randomised controlled trial /: does the provision of telephone support enhance the effectiveness of computer-delivered cognitive behaviour therapy? : a randomised controlled trial. (November 2016) - Brabyn, Sally
No abstract available